Thermophysical Properties of Electric Arc Plasma and the Wire Melting Effect with Lanthanum and Sulfur Fluorides Addition in Wire Arc Additive Manufacturing - Sergey G. Parshin; Peter Mayr (Metals, 2021)
Achieving a higher quality in wire arc additive manufacturing (WAAM) is a result of the development of welding metallurgy, the development of filler wires, and the control of the thermophysical properties of the electric arc. In this paper, the authors developed composite wires for WAAM with a Ni-LaF3, Ni-LaB6 coating. The addition of LaF3, LaB6, and SF6 increases specific heat, thermal conductivity, enthalpy, and degree of plasma ionization, which leads to the increase in the transfer of heat from the arc plasma to the wire and to the change in the balance of forces during wire melting. The increase in the Lorentz electromagnetic force and the decrease in the surface tension force made it possible to reduce the droplet diameter and the number of short circuits during wire melting. The change in the thermophysical properties of the plasma and droplet transfer with the addition of LaF3, LaB6, and SF6 made it possible to increase the welding current, penetration depth, accuracy of the geometric dimensions of products in WAAM, reduce the wall thickness of products, and refine the microstructure of the weld metal using G3Si1, 316L, AlMg5Mn1Ti, and CuCr0.7 wires.